The albumin-binding domain as a scaffold for protein engineering - Nilvebrant, Johan (Research Network of Computational and Structural Biotechnology (RNCSB) Organization, 2013)
The albumin-binding domain is a small, three-helical protein domain found in various surface proteins expressed by gram-positive bacteria. Albumin binding is important in bacterial pathogenesis and several homologous domains have been identified. Such albumin-binding regions have been used for protein purification or immobilization. Moreover, improvement of the pharmacokinetics, through the non-covalent association to albumin, by fusing such domains to therapeutic proteins has been shown to be successful. Domains derived from streptococcal protein G and protein PAB from Finegoldia magna, which share a common origin and therefore represent an interesting evolutionary system, have been thoroughly studied structurally and functionally. Their albumin-binding sites have been mapped and these domains form the basis for a wide range of protein engineering approaches. By substitution-mutagenesis they have been engineered to achieve a broader specificity, an increased stability or an improved binding affinity, respectively. Furthermore, novel binding sites have been incorporated either by replacing the original albumin-binding surface, or by complementing it with a novel interaction interface. Combinatorial protein libraries, where several residues have been randomized simultaneously, have generated a large number of new variants with desired binding characteristics. The albumin-binding domain has also been utilized to explore the relationship between three-dimensional structure and amino acid sequence. Proteins with latent structural information built into their sequence, where a single amino acid substitution shifts the equilibrium in favor of a different fold with a new function, have been designed. Altogether, these examples illustrate the versatility of the albumin-binding domain as a scaffold for protein engineering.